2016
DOI: 10.1088/1755-1315/37/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying rate of deforestation and CO2emission in Peninsular Malaysia using Palsar imageries

Abstract: Abstract.Increasing human population and the rapid grows of Malaysia's economy are often associated with various environmental disturbances which have been contributing to depletion of natural resources and climate change. The need for more spaces for numerous land development activities has made the existing forests suffer deforestation. The study was carried out in Peninsular Malaysia, which currently has about 5.9 million ha of forests. Phased array type L-band SAR (Palsar) and Palsar-2 images over the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Despite both the Pendrill et al (37) and Goldman et al (36) datasets indicating that oil palm expansion is also a key driver of recent deforestation in Malaysia, we find no national-level estimates of this in our literature review (see table S5). However, by combining the estimates of oil palm-driven deforestation in Peninsular Malaysia by (158) and in the Malaysia Borneo by (137), we estimate that just over 0.05 Mh/y of forests were converted to oil palm plantations in the 2010-2015 period. This estimate is similar to that of Pendrill et al (37) (0.05 Mha/y), but only a third of that of Goldman et al (36) (0.16 Mha/y) for the same time period.…”
Section: S6c Combined Evidence On Deforestation Attributed To Commodi...mentioning
confidence: 95%
See 1 more Smart Citation
“…Despite both the Pendrill et al (37) and Goldman et al (36) datasets indicating that oil palm expansion is also a key driver of recent deforestation in Malaysia, we find no national-level estimates of this in our literature review (see table S5). However, by combining the estimates of oil palm-driven deforestation in Peninsular Malaysia by (158) and in the Malaysia Borneo by (137), we estimate that just over 0.05 Mh/y of forests were converted to oil palm plantations in the 2010-2015 period. This estimate is similar to that of Pendrill et al (37) (0.05 Mha/y), but only a third of that of Goldman et al (36) (0.16 Mha/y) for the same time period.…”
Section: S6c Combined Evidence On Deforestation Attributed To Commodi...mentioning
confidence: 95%
“…a Brazil(130), Indonesia(55,114) b Brazil (131) c Brazil(80,132,133) d Indonesia(55,114,134,135); Malaysia(136,137) …”
mentioning
confidence: 99%
“…The state includes 74 forest reserves with 10 virgin forests, the largest of which is Taman Negara Pahang, a part of the Central Forest Spine blueprint [56]. Despite all efforts, forest conservation in Pahang remains ineffective, with oil palm development serving as one of the principal causes of deforestation, emitting 110.6 million Mg CO 2 across the Malaysian Peninsula between 2005 and 2015 [57,58]. Out of Malaysia's 5.87 million hectares of oil palm, 15% are planted in Pahang, which accounts for 23.4% of the state's GDP [59][60][61].…”
Section: Study Sitementioning
confidence: 99%
“…Additionally, it has been reported that encroachment (Noh et al, 2018), illegal development (Hashim et al, 2019), deforestation caused by agriculture (Hezri and Hasan, 2006;Hamdan et al, 2016;Sarmin et al, 2016), aquaculture (Hamdan et al, 2016;Sarmin et al, 2016), urban expansion (Aisyah et al, 2015;Islam et al, 2017;Hashim et al, 2019), pollution and excessive tourism activities (Sarmin et al, 2016;Islam et al, 2017), and mass tourism (Hashim et al, 2019) have endangered the biodiversity in many of these areas. These factors attributed to weaknesses in the implementation of management plans (Pourebrahim et al, 2015;Marzukhi, 2020) which is now adding pressure for Malaysia to move toward a more sustainable future.…”
Section: Ecosystem Protection Approachesmentioning
confidence: 99%